Managing Risk and Information Security: Protect to Enable (First Edition) - Malcolm W. Harkins (Apress, 2013)
Managing Risk and Information Security: Protect to Enable, an ApressOpen title, describes the changing risk environment and why a fresh approach to information security is needed. Because almost every aspect of an enterprise is now dependent on technology, the focus of IT security must shift from locking down assets to enabling the business while managing and surviving risk. This compact book discusses business risk from a broader perspective, including privacy and regulatory considerations. It describes the increasing number of threats and vulnerabilities, but also offers strategies for developing solutions. These include discussions of how enterprises can take advantage of new and emerging technologies-such as social media and the huge proliferation of Internet-enabled devices-while minimizing risk.